Accuracy and reproducibility of probe forces during simulated periodontal pocket depth measurements - K.N. Al Shayeb; W. Turner; D.G. Gillam (Saudi Dental Journal)
Aim: The aim of the present study was to measure the accuracy and reproducibility of probe forces in simulated assessments of periodontal pocket depth. The study included experienced and inexperienced examiners and used manual and pressure-sensitive probes. Materials and methods: Sixty-one participants were divided into seven groups and asked to probe selected anterior and posterior sites with three different probes (Williams 14W, Chapple UB-CF-15, and Vivacare TPS probes). The model was positioned on a digital electronic balance to measure force, which was recorded initially and after 15 min. Probe preferences were recorded. Accuracy was measured by comparing to a standardized 25 g force, and reproducibility was calculated for all duplicate measurements. Results: The Vivacare probe produced the most accurate and most reproducible forces, whereas the Williams probe produced the least accurate and least reproducible forces. Probe forces were lighter at anterior sites compared to posterior sites at baseline. Probe forces were reduced at both sites after 15 min compared to baseline. Conclusions: Vivacare TPS periodontal probes are more accurate and reproducible than Chapple and Williams probes. Many clinicians in this study preferred the Chapple probe. Keywords: Probing, Force, Periodontal probes, Reproducibility, Accuracy